2021
DOI: 10.31234/osf.io/65fmr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Boosting the impact of charitable giving

Abstract: We introduce a strategy to increase effective giving, combining three techniques: bundling, asymmetrical matching, and donor coordination. In a series of online studies, we experimentally demonstrate the effectiveness of the techniques. In an ongoing study, using a custom donation platform aimed at a mass audience (GivingMultiplier.org), we test them in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The evidence for the effectiveness of effectiveness information is mixed. Some studies have found no effect [74,75], while some of our own studies have found a large effect, increasing the proportion of effective donors from zero to 17% or even higher [21,76]. Other studies point to heterogeneity among donors, with minimal effects overall but larger effects for donors who are more altruistically motivated [77] and more educated, especially when encouraged to think more deliberately [78].…”
Section: Strategies To Increase Effective Givingmentioning
confidence: 86%
See 1 more Smart Citation
“…The evidence for the effectiveness of effectiveness information is mixed. Some studies have found no effect [74,75], while some of our own studies have found a large effect, increasing the proportion of effective donors from zero to 17% or even higher [21,76]. Other studies point to heterogeneity among donors, with minimal effects overall but larger effects for donors who are more altruistically motivated [77] and more educated, especially when encouraged to think more deliberately [78].…”
Section: Strategies To Increase Effective Givingmentioning
confidence: 86%
“…Combining these insights suggests a new strategy to increase the effectiveness of charitable giving: many donors may be amenable to splitting their donations between an emotionally appealing charity and a highly effective charity, especially if provided with effectiveness information. We have applied this technique in the design of an online donation platform (Giving Multiplier vi ), which uses matching funds (see earlier) to encourage donors to split their donations between a highly effective charity and their favorite charity [76].…”
Section: Splittingmentioning
confidence: 99%